Boiler water requirement for a selected local pharmaceutical factory: a brief case study: article - Amri, Nur Alya Natasha; Hanipah, Suhaiza Hanim; Hashim, Md Amin (2017)
This case study had been carried out in Ain Medicare Sdn Bhd, a local pharmaceutical factory that is located in Kelantan. In the factory, raw steams from boilers play an important role as heating agent in distillers and autoclaves. The raw steams are produced in the boilers by heating the feed water that is treated with some chemicals in order to make sure the water chemistry in the boiler is below limitation. As the raw steam produced by the boilers exceed the demand, the operating time for each boiler has to be reduced from 19 hours/day to 11.5 hours/day. Material balance on water and steam are required to determine the percentage of steam lost. Besides that, corrosion problem due to vaporization of steam during blowdown has to be minimize by using blowdown vessel. Therefore, blowdown vessel size are suggested to be about 2.5 meter height and 1.8 meter diameter with volume of cooling water is 10.97 m³ to 11.81 m³ in a day.